INCIDENCE OF THE PRIVATE SECTOR IN THE CURRICULUM BUILDING PROCESS: THE APPROPRIATION OF THE PUBLIC PURPOSES OF EDUCATION - Borghi, Raquel Fontes [UNESP] (Unesp-faculdade Ciencias & Letras, 2021)
In Brazil, as in many other countries, the presence of the private sector in education has been increasing exponentially, as pointed out by many studies. Such a movement for the advancement of the private sector in education can be understood in the movement of crisis and capitalist expansion. This article is a theoretical essay based on research carried out by the author in more than 15 years of studies on the theme of privatization of education. It aims to reflect on the incidence of the private sector in the curriculum construction process and to highlight that this movement has led to the sequestration of the public ends of education by business reformers. It points to the potential of democratic management as a possibility against hegemony in the perspective of defining public and collective ends for education.
Keywords: Curriculum; Commodification; Privatization; Democratic management